Propagandas hardsell: proposição e teste de um modelo integrativo - Fernandes, Aleixo (2021)
This thesis presents a proposal for an integrated framework for evaluating advertisements. The framework unites management aspects of creative elements - usually dispersed in marketing research - with the behavioural perceptions, attitudes and intentions generated by advertising. The proposed framework was validated with data collected through an online survey, counting on the evaluation of 15,186 respondents on 98 advertisements carried out by 4 major retailers in the consumer goods sector. Data analysis was performed using the SEM / PLS method, using the SmartPLS software. After validating the model (measurement and paths), only one out of 21 hypotheses was not confirmed. The main theoretical contributions resulting from the study are: 1-integration of the creative elements of advertising, a dimension that characterizes the possibility of managing the advertiser, with the perceptions of advertising, attitudes and intentions of the consumer forming the dimension that can be considered results of communication, always from the perspective of planned behavior; 2- evidenced the mechanisms by which the advertisements generate the desired effects by the advertisers in the consumers through two important management areas so that the advertising produces the expected effects: communication management and operation management; 3- test and validation of relationships involving the coherence of the speech and the credibility of the advertisement and the advertiser; 4- validation of the relationship between the credibility of the advertiser and the attitude towards advertising; 5- proposition and validation of the intention to visit as a mediator of consumer attitudes and behavioral intentions. At the end, 3 contributions to the practice are reported.